(untitled) (Physical Education, Health and Social Sciences, 2025)
An experiment was conducted to study the impact of temperature on embryonic development rates in Gallus gallus domesticus. For this purpose, 40 eggs were obtained and divided into four groups (10 eggs in each group): Group A was kept in a refrigerator at a temperature of approximately( 9-10°C), Group B was kept at normal room temperature (28–36°C), Group C was buried in flour (30–32°C), and Group D was kept wrapped in cotton (33–46°C). The experiment lasted 15 days, during which the eggs were observed daily to note changes in their weight, color, odor, and internal development (through candling). The results showed that there was no embryonic development at all in groups A and B, which may be due to the low or inappropriate temperature. In group C, 40% of the eggs showed signs of partial development, while in group D, 60% of the eggs showed clear embryonic development, but no complete chicks hatched in any of the groups. The study concluded that suitable, constant and high temperature is essential for proper embryonic development of eggs. Although home-made methods such as flour or cotton may be partially successful, a suitable arrangement such as an artificial incubator is indispensable for complete and safe hatching of chicks. Moreover, indigenous eggs are better adapted to local temperatures, which may allow for some successful incubation even in local resources.